A COMPARATIVE STUDY OF AHMAD IBN HANBAL AND IMAM AL-SHAWKANI ON HADITHS OF OBEDIENCE TO UNJUST RULERS: Between Political Stability and Moral Accountability - Palupi, Kamelia Hardaning; Rochmawati, Nikmah; Hikmah, Siti; Tsani, Fatimah Zulfa; Haq, Giovani Jadal (Ilmu Hadis, Fakultas Ushuluddin, Universitas Islam Negeri (UIN) Sunan Kudus, 2026)
Obedience to rulers constitutes an important theme in hadith studies because of its close relationship with the political stability and social order of the Muslim community. This article compares the perspectives of Ahmad Ibn Hanbal and Imam al-Shawkani regarding hadiths on obedience to unjust (zhalim) leaders. It analyzes how both scholars evaluate the authenticity of these traditions through sanad and matan criticism and examines the interpretive implications of their understanding and application. Employing a qualitative method based on library research with a comparative approach, the study uses Usul al-Sunnah by Ahmad Ibn Hanbal and Nayl al-Awtar by Imam al-Shawkani as primary sources. The data are analyzed descriptively and comparatively to highlight differences in their approaches to both riwayah (assessment of chains of transmission and textual quality) and dirayah (interpretation and practical implications). The findings reveal that Ahmad Ibn Hanbal emphasized near-absolute obedience to rulers in order to preserve political stability and prevent fitnah, permitting disobedience only when rulers explicitly command disbelief. In contrast, Imam al-Shawkani advocated conditional obedience and recognized the legitimacy of criticizing and rejecting policies that contradict Islamic law. By comparing two prominent scholars from different historical periods, this study demonstrates that the understanding of hadiths on leadership is not fixed or absolute but rather dynamic and shaped by varying social and political contexts. Ketaatan kepada pemimpin merupakan salah satu tema penting dalam kajian hadis karena memiliki hubungan yang erat dengan stabilitas politik dan tatanan kehidupan umat Islam. Artikel ini membandingkan pandangan Ahmad Ibn Hanbal dan Imam al-Syaukani mengenai hadis-hadis tentang ketaatan kepada pemimpin yang zhalim. Kajian ini menganalisis bagaimana kedua tokoh tersebut menilai autentisitas hadis melalui kritik sanad dan matan, serta menelaah implikasi interpretatif dari pemahaman dan penerapannya. Penelitian ini menggunakan metode kualitatif berbasis studi kepustakaan dengan pendekatan komparatif. Sumber data utama berasal dari Usul al-Sunnah karya Ahmad Ibn Hanbal dan Nayl al-Awtar karya Imam al-Syaukani, yang dianalisis secara deskriptif dan komparatif untuk mengungkap perbedaan pendekatan keduanya dalam aspek riwayah (penilaian terhadap rantai periwayatan dan kualitas teks) serta dirayah (penafsiran dan implikasi praktis). Hasil penelitian menunjukkan bahwa Ahmad Ibn Hanbal menekankan ketaatan yang hampir bersifat mutlak kepada penguasa demi menjaga stabilitas politik dan mencegah fitnah, dengan pengecualian ketika penguasa secara jelas memerintahkan kekufuran. Sebaliknya, Imam al-Syaukani menegaskan bahwa ketaatan bersifat kondisional dan mengakui legitimasi untuk mengkritik bahkan menolak kebijakan penguasa yang bertentangan dengan syariat Islam. Dengan membandingkan dua ulama terkemuka dari periode sejarah yang berbeda, penelitian ini menunjukkan bahwa pemahaman terhadap hadis-hadis tentang kepemimpinan tidak bersifat tetap dan absolut, melainkan dinamis serta dipengaruhi oleh konteks sosial dan politik yang melingkupinya.